Efektivitas Sistem Pelayanan Pembayaran Retribusi Bulanan Toko di Unit Pelayanan Teknis Daerah Pasar Raya Kota Padang - Muhammad Rizki Afdal; Adil Mubarak (YASIN, 2026)
The advancement of technology has encouraged UPTD Pasar Raya Kota Padang to implement an electronic system for monthly store levy payments through QRIS as an effort to enhance the efficiency, transparency, and accountability of levy management. However, various technical, administrative, and social problems have emerged in its implementation, indicating the need for an in-depth examination of the effectiveness of this service system. This study aimed to analyze the effectiveness of the monthly store levy payment service system at UPTD Pasar Raya Kota Padang using the indicators of goal attainment, integration, and adaptation based on Duncan’s effectiveness theory within Richard M. Steers’ framework. This research employed a qualitative method with a descriptive approach. Data were obtained through observation, in-depth interviews, and document study, and were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings show that the monthly store levy payment service system is relatively effective, as reflected in the ease and speed of service through electronic payments, improved transparency of transaction recording, and well-functioning internal coordination. Nevertheless, this effectiveness has not yet been fully optimal due to constraints such as network disruptions, limited understanding of electronic payment systems among traders, and traders’ economic conditions that affect payment compliance. These findings underscore the need to improve technological quality, intensify outreach activities, and strengthen supervision so that the electronic levy payment service system can operate more optimally and sustainably in supporting efficient, transparent, and accountable levy management.